Construction and spatio-temporal derivation of hazardous chemical leakage disaster chain. (2nd October 2021) - Zheng, Xinxin; Wang, Fei; Jiang, Wenyu; Zheng, Xiaocui; Wu, Zuhe; Qiao, Xiaohui; Meng, Qingxiang; Chen, Qingguang
ABSTRACT: Hazardous chemicals are indispensable substances for the development of modern industries. However, improper storage, transportation, or handling of hazardous chemicals can cause chain disasters such as leakage and explosion, seriously threatening the safety of people's lives, society, economy, and natural environment. In this study, we analysed the occurrence and evolution process of various disaster events caused by hazardous chemical leakage based on the disaster system theory, and constructed a hazardous chemical leakage disaster chain from the aspects of disaster-causing factors, disaster-pregnant environment, hazard-affected bodies, and post-disaster losses. Taking a methane leakage accident as a case study, we conducted numerical simulation and spatio-temporal dynamic derivation on the hazardous chemical leakage disaster chain in a three-dimensional (3-D) geographic scene. This study can provide support on handling hazardous chemical leakage disasters and assist informed decision-making, including monitoring, pre-warning, disaster forecast and prevention, emergency preparedness, and post-disaster response, further improving the efficiency of emergency response and urban safety management.